Species diversity pattern of mosquitoes (Diptera: Culicidae) breeding in different permanent, temporary and natural container habitats of Peshawar, KP Pakistan - Lubna; S. B. Rasheed; F. Zaidi (Brazilian Journal of Biology, 2023)
Abstract To determine the species composition, relative abundance and seasonal variation of different mosquitoes Genera (Aedes, Anopheles, Armigeres, Culex, and Culiseta) in different habitats the present research work was carried out in Entomology Research Laboratory of The University of Peshawar. Sampling performed from variety of permanent and temporary breeding habitats was carried out on monthly basis from targeted breeding sites for two consecutive years through dipping method. Species diversity in the survey sites was noted. Collection from these seventeen various types of potential larval habitats, yielded a total of 42,430 immature constituting 41,556 larvae and 874 pupae. Among these only 19,651 adult mosquitoes emerged comprising 11,512 female and 8,139 male mosquitoes. 78% (n= 15333) of mosquito larvae were from permanent and 22% (n=4318) were from temporary breeding sites. This study showed that Peshawar valley harbours 15 species from the genera Aedes, Anopheles, Armigeres, Culex and Culiseta. When the density of each species was examined, Culex quinquifasciatus was found to be dominant (79%) and constant in distribution. Among the temporary habitats Aedes albopictus was found as the most prevalent species particularly from tree holes and water cisterns. The highest intensity of mosquitoes was in June (2243 emerged adults) and November (2667 emerged adults) while the lowest was in January (203 emerged adults). A perfect positive correlation (r = +0.8) was found between temperature and population of mosquitoes (df 10 and α 0.05). The species diversity index for mosquitoes remained between 0.12 and 1.76. The Margalef’s richness components was noticeably low for bamboo traps (0.2) and fairly high for rice fields, Percolating water and Animal tracks (1.3) which shows the abundance of mosquito species in these habitats. Similarly Pielou’s Evenness was highest for bamboo traps (E=1) showing species uniform distribution. Animal tracks were presumed not only the diverse habitat rather also possessed high value for species richness and species evenness. Temperature, rainfall, humidity and other related attributes responsible for species variation and abundance need to be analysed further to pave way for controlling vector species in their oviposition targeted sites.